2020
DOI: 10.1017/brimp.2020.6
|View full text |Cite
|
Sign up to set email alerts
|

‘We struggle and muddle.’ A qualitative study exploring community ABI therapists’ experiences of using, training in and implementing behaviour interventions

Abstract: Objectives: Individuals with acquired brain injury (ABI) may present with challenging behaviours (CB) that place themselves and others at risk of harm and impact their community integration. It is crucial for community ABI therapists to successfully train in and implement behaviour interventions. The current study aimed to investigate community ABI therapists’ experiences of using, training in and implementing behaviour interventions. An additional aim was to determine these therapists’ understanding of P… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0

Year Published

2021
2021
2025
2025

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 48 publications
0
4
0
Order By: Relevance
“…Additionally, only a minority considered they would be approved by the Commission as a proficient or advanced behaviour support practitioner. This adds to recent findings of research with the broader ABI workforce in Australia, which highlighted clinicians' limited understanding of, and lower confidence in, provision of PBS (Carmichael et al, 2020;Carmichael et al, 2021).…”
Section: Discussionmentioning
confidence: 60%
See 2 more Smart Citations
“…Additionally, only a minority considered they would be approved by the Commission as a proficient or advanced behaviour support practitioner. This adds to recent findings of research with the broader ABI workforce in Australia, which highlighted clinicians' limited understanding of, and lower confidence in, provision of PBS (Carmichael et al, 2020;Carmichael et al, 2021).…”
Section: Discussionmentioning
confidence: 60%
“…Finally, this research has further demonstrated the specialised skills required in both service planning and provision in the area of behaviour support, and the need to ensure equity of access to the NDIS supports including behaviour support services (Carey et al, 2018; Carmichael et al, 2021; Gould et al, 2021). Meaningful behaviour change can take years after an ABI, and as such a life-span perspective is required for funding of behaviour supports within plans beyond just a one-off or single year of funding allocation.…”
Section: Discussionmentioning
confidence: 82%
See 1 more Smart Citation
“…[19][20][21] However, the implementation of such programs remains difficult. Stakeholders of Positive Behaviour Support programs raise potential issues such as lack of time, money, staff, or Positive Behaviour Support training in rehabilitation teams, 22 as well as the length or intensity of programs that may restrict the participation of family caregivers and individuals with TBI, 20 and hinder their engagement in those programs over the long-term. 23 Furthermore, challenging behaviours are context-specific and shaped or triggered by various internal (e.g., fatigue or stress levels) and external factors (e.g., punitive or avoidant responses from formal or informal caregivers, complex task demands), [24][25][26] and individuals vary in their ability to regulate behaviours from one situation to another.…”
Section: Introductionmentioning
confidence: 99%